Mechanical Properties of High Performance Fiber Reinforced Concrete - Wasan Ismail Khalil; Ikbal Naeem Gorgis; Zeinab Raad Mahdi (Engineering and Technology Journal, 2013)
An experimental work was carried out to produce high performance concrete (HPC) using superplasticizer and silica fume reinforced with fiber. The variables studied were fibers type (steel fibers and polypropylene fibers), aspect ratio of steel fibers (60 and 100) and fiber volume fraction (0.0%, 0.5%, and 0.75%). The effect of fibers on the mechanical properties (compressive strength, splitting tensile and flexural strength, static modulus of elasticity, toughness, and resilience) of normal strength and high performance concrete was also studied. The results show that the optimum dosage of silica fume is 5% as addition by weight of cement with superplasticizer dosage 2 liter/100kg of cement. This dosage of silica fume improves the compressive strength of concrete by about 25% relative to concrete mix without silica fume. The addition of steel fibers causes a slight increase in compressive strength of HPC as fiber volume fraction increases, while the compressive strength decreases as fiber aspect ratio increases. Both splitting tensile and flexural strengths show a significant increase as the fiber volume fraction and aspect ratio increases. The percentage increase in compressive, splitting tensile and flexural strengths for HPC with steel fiber volume fraction 0.75% and aspect ratio 100 at age 60 days is about 9%, 75%, 64%, while for HPC containing polypropylene fiber with volume fraction 0.5% is about 8.5%, 2%, 0% respectively relative to non fibrous HPC.